Th2 cell-specific cytokine expression and allergen-induced airway inflammation depend on JunB - Hartenstein, Bettina; Teurich, Sibylle; Heß, Jochen; Schenkel, Johannes; Schorpp-Kistner, Marina; Angel, Peter (The EMBO journal, 2002)
Naïve CD4+ T cells differentiate into effector T helper 1 (Th1) or Th2 cells, which are classified by their specific set of cytokines. Here we demonstrate that loss of JunB in in vitro polarized Th2 cells led to a dysregulated expression of the Th2-specific cytokines IL-4 and IL-5. These cells produce IFN-? and express T-bet, the key regulator of Th1 cells. In line with the essential role of Th2 cells in the pathogenesis of allergic asthma, mice with JunB-deficient CD4+ T cells exhibited an impaired allergen-induced airway inflammation. This study demonstrates novel functions of JunB in the development of Th2 effector cells, for a normal Th2 cytokine expression pattern and for a complete Th2-dependent immune response in mice.
Gesehen am 05.05.2021